Tantangan Bimbingan Keagamaan Bagi Muallaf Yayasan Atthoharoh di Sidamanik Kabupaten Simalungun - Ilham, Sai Amanda (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
This research is entitled "The Challenge of Religious Guidance for Muallaf of the At-Thoharoh Foundation in Sidamanik, Simalungun Regency". The existence of the At-Thoharoh Foundation in Sidamanik, Simalungun Regency provides new hope for converts to no longer worry about practicing their Islam, no more feelings of being left out and, of course, no longer returning to apostasy (returning to their old religion) because they find that Islam is a religion that brings peace for its adherents. In addition, the faith of converts as a Muslim is good and correct, so that converts who truly have strong faith are realized. The purpose of this study is to find out how a convert enters the teachings of Islam and to find out how the At-Thoharoh Foundation's religious guidance method for converts is to improve their abilities and the basis for understanding faith. The research method used by researchers is an anthropological approach. The Anthropological Approach is a point of view or way of looking at a problem of concern but also includes an understanding of research methods or techniques that are appropriate to that approach. Judging from the type of this research in the form of field research (field research), Data Sources, in this case the researcher classifies sources into two categories, namely primary sources and secondary sources. Data Collection Techniques. Data collection techniques are the most important steps in research. When viewed from the point of view of data collection methods or techniques, data collection techniques can be carried out by observation, interview (interview), and documentation. Based on the results of the research, the authors obtained the results of the Religious Guidance Method of converts at the At-Thoharah Foundation, namely the Lecture Method. The lecture method is a guidance technique that provides several direct explanations which are heavily colored with the characteristics and texture style of speaking of a da'I or sutadz. Routine Recitation Method, Al-Hikmah (Wise) Method, Al-Hikmah (Wise) Method One of the meanings of wisdom in preaching is to place converts according to predetermined levels and support new converts. Supporting new converts is an appreciation and a sense of care for converts . This is done to avoid alienation after being shunned by their family environment.